The Implementation of Comic Strips Media And Think Pair Share Strategy in Teaching Reading Comprehension at Eight Grader of At-Thohiriyyah Junior High School - Hibatullah, Muhammad Naafi; Mulyadi, Dodi; Aimah, Siti (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study aimed to determine the implementation of the Think Pair Share strategy and comic strip media to improve the reading comprehension ability of students in jouniur high school. The study used a quantitative approach with the Classroom Action Research method, which was carried out in two cycles. Each cycle consisted of the stages of planning, action implementation, observation, and reflection. Data collection techniques were conducted through pre-tests and post-tests. The results showed a significant increase with the paired sample t-test in Cycle I revealed a significant difference between pre-test and post-test scores (t = -3.973, p 0.05. This indicated that the Think Pair Share strategy, assisted by comic strips, effectively improved students' reading comprehension ability. Therefore, Think Pair Share strategy assisted by comic strip media is an empirically supported instructional approach for improving reading comprehension in junior high school English education.